Kejadian Stunting Pada Anak Usia Prasekolah (3-5 Tahun) Berdasarkan Status Sosial Ekonomi Dan Penyakit Infeksi - Rokhman Abdul; Qorriuyu Nana (Jurnal Kesehatan, 2020)
Background: Stunting is a length or height that is more than minus two standard deviations of the WHO child growth standard which starts in the development process of the fetus in the womb until the age of 2 years with both short and long term effects. Research Objectives: This study aims to analyze the relationship between socioeconomic status and infectious diseases with the incidence of stunting in preschool children in Sugihwaras District, Bojonegoro Regency. Methods: This study used a correlation analytic design with a retrospective cohort approach. The study was conducted in February-March 2020. The sample was taken by a random sampling technique. A sample of 36 preschool-aged stunting children. Data were analyzed using logistic regression. Results: showed a relationship between socioeconomic status (P = 0.000) and the incidence of stunting. there is an association of infectious diseases (P = 0.000) with the incidence of stunting. However, in the logistic regression test, it was found that there was a relationship between socioeconomic status (p = 0.012) and there was no relationship between infectious diseases (p = 0.071) and the incidence of stunting. Conclusions and Suggestions: Preschoolers with middle to lower socioeconomic status are 30,549 times more likely to experience stunting than preschool children with upper-class socioeconomic status. It is hoped that the research results can provide additional information to change the family mindset regarding the incidence of stunting.